Molecular Testing on Cytology for Gene Fusion Detection - Schmitt, Fernando; Di Lorito, Alessia; Vielh, Philippe (Frontiers in Medicine, 2021)
Cytology samples are suitable for the study of genotypic and phenotypic changes observed in different tumors. Being a minimally invasive technique, cytology sampling has been used as an acceptable alternative to track the alterations associated with tumor progression. Although the detection of gene mutations is well-established on cytology, in the last few years, gene fusion detections are becoming mandatory, especially in some tumor types such as lung cancer. Different technologies are available such as immunocytochemistry, fluorescence in situ hybridization, reverse transcription-polymerase chain reaction, and massive parallel sequencing approaches. Considering that many new drugs targeted fusion proteins, cytological samples can be of use to detect gene fusions in solid and lymphoproliferative tumor patients. In this article, we revised the use of several techniques utilized to check gene fusions in cytological material.